Coherent GNSS Reflections over the Sea Surface: A Classification for Reflectometry - Semmling, Maximilian; Gerland, Sebastian; Gerber, Thomas; Ramatschi, Markus; Dick, Galina; Wickert, Jens; Hoque, Mohammed Mainul (2020)
The exploitation of GNSS signals for reflectometry opens several fields of application over the ocean, land and in the cryosphere. Coherence of the reflection allows precise measurements of the carrier phase and signal amplitude for accurate sea surface altimetry and sea ice characterisation. A coherence condition can be set by a threshold of the signal-to-noise power ratio (SNR). Previous simulations suggest that an SNR > 30 dB will ensure a coherent processing of the signal. This paper presents reflectometry measurements that provide signal coherence information. The measurements have been conducted on two research vessels: R/V Lance and R/V Polarstern. The objective is to reveal the required conditions for coherent reflectometry depending on sea state and sea ice occurrence. Three data sets from expeditions of the two research vessels to Fram Strait, the Northern Atlantic and the Arctic Ocean are analysed. On both ships a GORS (GNSS Occultation Reflectometry Scatterometry) receiver with three antenna links has been installed. A common up-looking link is dedicated to direct signal observations. Two additional side-looking links allow sampling the reflected signal with right- and left-handed polarization (RHCP and LHCP). The respective setups have suitable positions to observe grazing sea surface reflections (< 30 deg elevation angle). The antennas are mounted on Lance and Polarstern about 24 m and 22 m above sea level, respectively. Reflection events are recorded continuously covering more than 70 days. Each event comprises a track of the satellite signal in the grazing angle elevation range. On average 2-3 reflection events were recorded in parallel. The results of the analysis show that in coastal waters (German Bight and Svalbard fjords) up to 44%, 37% (RHCP, LHCP) of the measurements meet the coherence condition. On the high sea it is rarely met, only <0.5% of RHCP and LHCP records fulfill the coherence condition there. The rate of coherent observations increases up to 14%, 13% (RHCP, LHCP) in ...